2012
DOI: 10.3390/medicina48050037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nanoparticles in Rats During Critical Periods of Pregnancy

Abstract: Background and Objective. Nanotechnology works with substances at a nanometer scale, and it offers many solutions for biomedicine. Nanoparticles (NPs) have been shown as effective agents for imaging, drug delivery, pathogen detection, etc. However, to date, NP toxicity is poorly known. The aim of our study was to investigate the embryotoxicity and teratogenicity of quantum dots (QDs) at the different stages of rat embryogenesis. Materials and Methods. Wistar rats were injected with CdSe/ZnS or CdTe QDs on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In the previous researches, the results of QDs toxicity evaluations on embryo was usually associated with the efficiency of the placenta as barrier. Zalgeviciene et al saw the presence of CdSe/ZnS QDs in the uterus and placenta, but not in embryonic tissues in animals injected with QDs at 13th day of embryogenesis, and found no direct embryotoxicity or teratogenic effects [30]. In the study of Chu et al, a large amount of Cd was detected in the pups after maternal injection with MPA-coated QDs at late pregnancy, and the Cd content increased with increasing injection dosage [9].…”
Section: Discussionmentioning
confidence: 96%
“…In the previous researches, the results of QDs toxicity evaluations on embryo was usually associated with the efficiency of the placenta as barrier. Zalgeviciene et al saw the presence of CdSe/ZnS QDs in the uterus and placenta, but not in embryonic tissues in animals injected with QDs at 13th day of embryogenesis, and found no direct embryotoxicity or teratogenic effects [30]. In the study of Chu et al, a large amount of Cd was detected in the pups after maternal injection with MPA-coated QDs at late pregnancy, and the Cd content increased with increasing injection dosage [9].…”
Section: Discussionmentioning
confidence: 96%
“…However, there is some evidence suggesting that certain NPs cannot pass through the PB. CdTe QDs coated with polyethylene glycol or mercaptopropionic acid, for example, were injected into Wistar rats, and subsequent penetration through the placental barrier was observed [ 94 ]. These QDs were mostly found in the complex cell structure of the placenta [ 94 ].…”
Section: The Possible Ways For Nps Across the Pbmentioning
confidence: 99%
“…There are many studies in this field [109][110][111], but the detailed effects of NPs still pose many questions. A decrease in embryonic weight after QDs injection on the sixth day of embryogenesis (CdSe/ZnS QDs, 9.6%; CdT QDs, 6.2%) has been reported, and no embryotoxic or teratogenic effects were observed at any stage of embryogenesis [112]. Others have shown that NPs (nSP and TiO2s 70 nm and 35 nm in diameter, respectively) can cross the placental barrier in pregnant mice and cause neurotoxicity in their offspring [113].…”
Section: Pharmacokinetics Of Cadmium-containing Quantum Dotsmentioning
confidence: 98%